Optimization of Seed-Receiving Mechanism in Belt-Driven Seed Guide Tube Based on High-Speed Videography Experiment - Chengcheng Ma; Zhihuan Zhao; Xiaomei Chen; Youyuan Tang; Ning Song; Yanfeng Xiao; Xu Yang (Agriculture)
During high-speed corn sowing at 10 km/h, the rapid seed discharge resulting from the high rotation speed of the seed disc escalates the impact force of seeds as they are released from the seed metering device into the seed guiding apparatus, consequently diminishing the overall seeding efficiency of the seeder. This study employed high-speed videography to conduct experiments and optimize parameters for the seed-receiving mechanism of a belt-driven seed guide tube. By changing the clamping wheel speed and seed-receiving angle, the speed change curve and displacement trajectory of seeds under different conditions were obtained and analyzed. The findings demonstrate that the seed speed fluctuation is more stable, and the seed displacement trajectory achieves greater stability at a clamping wheel speed of 560 r·min−1. When the seed-receiving angle is set at 85°, the seed speed fluctuation becomes less apparent, resulting in a smoother seed displacement trajectory. Finally, the experimental results of high-speed cameras are confirmed by field tests. The findings of this study can act as a theoretical basis for the further optimization of the experimental belt-driven seed guide tube.